PROFIL KEMAMPUAN LITERASI SAINS MAHASISWA CALON GURU SEKOLAH DASAR - Y Nurhayati; W Sopandi; R Riandi (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the profile of the scientific literacy competence of pre-service elementary school teacher students. The method used is descriptive quantitative method. The samples are 52 elementary school teacher education students at a private university (23 students from class AO1 and 29 students from class AO2). The instrument used is the scientific literacy ability test questions consisted of 80 multiple choices questions that have passed the validity test. The data were then analyzed by using descriptive statistical analysis. The results showed that the scientific literacy competence of pre-service elementary school teacher students was in the moderate category. In details, the sub-indicator of explaining scientific phenomena is in the moderate category, identifying scientific questions or issues is in the moderate category, and using scientific evidence is in the low category. The results show that overall the sub-indicators are in the moderate category.